TLR2 and TLR4 in Cutaneous Leishmaniasis Caused by Leishmania major. (27th October 2013) - Tolouei, S.; Hejazi, S. H.; Ghaedi, K.; Khamesipour, A.; Hasheminia, S. J.
Abstract: Cutaneous leishmaniasis (CL) is a self‐healing skin disease which rarely for unknown reason(s) the lesion develops to a non‐healing form. It seems that the initial contact of Leishmania parasites with the host innate immune system is an important step in the outcome of the disease. Recent studies suggested that toll‐like receptors (TLRs) play a role in Leishmania recognition. In this study, the level of TLR2 and TLR4 was checked in patients with healing form of lesion and compared with that of patients with non‐healing form of lesion caused by Leishmania major . Gene expression of TLR2 and TLR4 in peripheral blood‐derived macrophages, before and after stimulation with live L. major promastigotes, was evaluated using quantitative real‐time reverse transcription PCR and flow cytometry. The results showed that the mean relative gene expression and difference membrane expression of TLR2 in macrophages of patients with healing form of lesion were significantly higher than patients with non‐healing form of lesion ( P  < 0.0001 and P  = 0.0034), respectively, and the mean relative gene expression and difference in protein expression of TLR4 in macrophages of patients with healing form of lesion were significantly higher than that of patients with non‐healing form of lesion ( P  = 0.021 and P  = 0.002), respectively. The data suggested a possible role for TLR2 and TLR4 in the outcome of CL lesion. Further studies are needed to understand more about the detail role of the immune factors in leishmaniasis.